The relevance of prior use in trade mark conflicts - Alberts, Riaan Willem (University of South Africa, 2009)
This thesis investigates the role of prior use in common and statutory trade mark law. In the United States a pertinent requirement is priority of use. In the United Kingdom and South Africa, a reputation must be present. In the United Kingdom a plaintiff is required to have goodwill in the country, but in the United States and South Africa it is not required. The conception of a mark does not qualify for protection. It is not required that a business must have actually entered the market. In the United States the general approach is that a plaintiff will not receive protection in a remote area, but regard must be had to zones of natural expansion. British and South African law is the same, and protection may be obtained in areas where there is no trading. Where a dual reputation exists, neither party will be able to act against the other. The mere fact that the user of a mark was aware of the use thereof by another person, does not exclude protection. A trade mark application can be opposed on the basis of another application, combined with use of a mark, or on the ground of prior use. In some instances the fact that a mark has been filed will influence the burden of proof. In general, a registration can be expunged on the same grounds as would constitute grounds of opposition. The concurrent use of a mark can form the basis for the registration of a mark. In the United States, the use must have taken place prior to the filing date of the other party, but in the United Kingdom and South Africa, prior to the own filing date. In the latter two countries, knowledge of a mark is not necessarily exclusionary. Prior use is generally accepted as a defence to an infringement action. It is, however, noted that in various countries, it is only use prior to the relevant date that will be protected, and there is not necessarily a right to extend the scope of use concerned.
Keywords: Common law trade marks; Competencia; Competition law; Intellectual property; Trade marks; Unfair competition; Unlawful competition

A tutela jurídica do capital intelectual das sociedades empresárias - Abdallah, Ana Claudia Karam (Universidade de São Paulo, 2009)
Na atual era pós-industrial, o conhecimento passa a ser o principal fator de produção da economia. De fato, ele confere à empresa seu maior diferencial competitivo no mercado globalizado: a inovação, ou seja, a capacidade de, continuamente, gerar novos produtos, processos e serviços ou aperfeiçoar os existentes. A organização da empresa em sociedade empresária possibilita a criação de conhecimento coletivo oriundo do trabalho profissional dos seus sócios, administradores e empregados, fato que originou a expressão capital intelectual, cunhada no âmbito econômico para designar o patrimônio empresarial de natureza intangível resultante de contribuições intelectuais. Como o Direito é precedido da evolução das sociedades e da Economia, nota-se a importância de sempre se buscarem soluções jurídicas às novas realidades socioeconômicas que surgem ao longo da história. Diante disso, a análise da natureza jurídica e das formas de tutela do capital intelectual torna-se imperativa para a identificação e apropriação privada desse patrimônio pela sociedade empresária, seja por meio do exercício de direitos de exclusivo, seja pela implementação de mecanismos de governança capazes de assegurar a diferenciação da atividade empresarial no mercado e a necessária coibição de práticas de concorrência desleal. In the current post-industrial age, knowledge becomes the main production factor of the economy. Indeed, it provides the company with its main competitive advantage in the globalized market: the innovation, that is, the capacity of continuously generating new products, processes and services or enhance the existing ones. The companys organization as business company allows the creation of collective knowledge arising from the professional work of its partners, officers and employees, which fact originated the term intellectual capital, created in the economic scope to designate the corporate equity of intangible nature resulting from intellectual contributions. As the Law came after the evolution of the companies and of the Economics, it is noted the importance of the constant search for legal solutions, the new socioeconomic realities that appear along the history. In view of that, the analysis of the legal nature and of the forms of protection of the intellectual capital becomes critical for the identification and private appropriation of such equity by the business company, either by means of the exercising of exclusive rights or by the implementation of governance mechanisms capable of ensuring the differentiation of the corporate activity in the market and the required restraining of unfair competition practices.
Keywords: Capital social; Concorrência desleal; Direito empresarial; Estabelecimento comercial; Intangible; Intellectual capital; Intellectual property; Propriedade intelectual; Sociedade comercial; Unfair competition

La qualification des contrats d'auteur - Raimond, Sébastien (Université Paris Est, 2008)
La qualification du contrat au regard du droit d’auteur met en exergue un renversement de la logique présidant habituellement à la construction des catégories contractuelles : les divers contrats nommés et, au-delà, tous les contrats d’auteur, sont moins définis par égard à leurs effets, à savoir le transfert de droit et les obligations qui en sont la contrepartie, que par référence à leur environnement. En effet, alors que l’effet translatif est commun à tout contrat d’auteur, sa qualification dépend avant tout de son environnement « matériel », c’est-à-dire du type d’oeuvre de l’esprit ou de droit d’exploitation visés au contrat, ou de son environnement humain, c’est-à-dire la qualité des parties, notamment celle d’auteur. À l’inverse de la qualification du contrat au regard du droit d’auteur, celle du contrat d’auteur au regard du droit civil dépend plus de ses effets que de son environnement, ce qui s’avère logique dès lors que les catégories contractuelles du code civil ne sont pas définies en fonction de ce dernier. Dès lors que la nature du droit d’auteur ne constitue pas un obstacle aux qualifications civiles, les effets du contrat constituent les seuls critères de distinction opératoires. Lorsque l’obligation d’exploiter ne peut être réduite à une obligation accessoire, la qualification de vente ne peut qu’être évincée. Les modalités de la maîtrise de l’exploitation font alors apparaître que les contrats d’édition, de représentation et de production audiovisuelle sont en réalité, le plus souvent, des contrats de bail.
Keywords: Author's contract; Contrat d'auteur; Copyright; Droit d'auteur; Droits voisins; Intellectual property; Propriedade intelectual; Propriété intellectuelle; Qualification; Qualification (droit)

Essai sur une théorie générale en droit d'auteur - Haddadin, Suhail (Université de Poitiers, 2008)
This study proposes a critical reading of the contemporary doctrinal and jurisprudential currents that under the influence of the Anglo-Saxon system make back-move on the fundamental concepts of author's right. It aims to show that the property of the author on his work is not a legal dogma, but a result of the general principles of the French civil law, even of the entire French legal system. From where, the idea that the moral right in its traditional structure, finds a base adequate in the French Civil code. The current debate, which opposes the "romantic" and pragmatic doctrines, provides the discussion thread of the development of a general theory of author's right.
Keywords: Abusus; Author's right; Droit d'auteur; Droit moral; Epuisement du droit de divulgation; Individualism; Individualisme; Intellectual property; Intérêt général; Jürgen Habermas; Legal theory; Moral Right; Philosophie du droit d'auteur; Private sphere/Public sphere; Propriété artistique; Propriété intellectuelle; Propriété littéraire; Sphère privée/Sphère publique; The Exhaustion of the right of disclosure; The philosophy of author's right; Théorie générale; Utilitarianism; Utilitarisme; Études comparatives

Les sociétés de gestion collective : contribution à l'étude du lien entre sociétés et auteurs ou artistes-interprètes adhérents - Balsan, Laurie (Université Jean Moulin Lyon 3, 2007)
Les mérites de la gestion collective sont immenses. Les auteurs et artistes-interprètes sont le plus souvent des individus isolés. Pour eux, le libre jeu du marché aurait de fortes chances de se traduire par des conditions de rémunération misérables. L'ensemble de la doctrine s'accorde d'ailleurs à dire que le choix d'une gestion individuelle des droits serait source de difficultés pratiques considérables pour l'auteur ou l'artiste « isolé ». L'impuissance des titulaires de droits à effectuer eux-mêmes cette gestion commande donc, en pratique, de recourir à une société de gestion collective. Il est possible de soumettre une définition des sociétés de gestion collective formulée comme suit : « sociétés civiles particulières dont les associés présentent la qualité de titulaires de droits de propriété littéraire et artistique ; droits, par eux mis en commun, dans le but de les voir administrer. La mission de gestion collective à la charge de ces sociétés consiste principalement dans le contrôle et la défense desdits droits, la promotion des intérêts de leurs membres, et surtout, la délivrance, pour le compte de leurs adhérents, d'autorisations d'exploitation, puis la perception des rémunérations qui s'y rattachent et leur répartition ». De façon évidente, ces sociétés se trouvent au carrefour de multiples droits. Pour résumer, sur une base de droit commun interagissent non seulement le droit de la propriété littéraire et artistique et le droit des sociétés, mais aussi le droit des biens, le droit de la concurrence, le droit communautaire, et d'autres droits spéciaux à des degrés différents. En outre, si l'on se réfère à certains arrêts, il semble qu'il existe un régime spécifique, propre aux SGC, une sorte de droit « ultra spécial » : le « droit des SGC ». Pour le cas des SGC, le cloisonnement du droit en différents droits spéciaux mène à un régime flou et parfois parfaitement incohérent dont elles paraissent tirer profit en pratique. La finalité de cette thèse est d'éclaircir l'ensemble des règles applicables aux SGC et plus précisément au lien tissé entre la société et ses adhérents. L'objectif de ces travaux est de faire ressortir, s'agissant de ce rapport, un régime juridique cohérent. Quels sont les droits qui ont vocation à s'appliquer aux SGC et comment arriver à une complémentarité cohérente entre eux ? Il s'agit donc d'un travail de rationalisation qui impose de remettre en cause le droit applicable aux SGC et de le repenser « de lege ferenda ».
Keywords: Competencia; Concurrence; Contrats de gestion; Corporate law; Droit d'auteur; Droit des biens; Droit des sociétés; Intellectual property; Propriedade intelectual; Propriété intellectuelle

Licensavtalet och konkurrensrätten - Gölstam, Carl Martin (Uppsala universitet, 2007)
The purpose of this thesis is to describe and analyse the significance of economic thinking and arguments in the treatment of licence agreements in EC competition law. A central question is to what degree the concept of competition in EC law reflects an economically realistic approach to competition. The study also investigates to what degree the economic functioning of intellectual property is considered in competition regulation and how much the economic functioning of the licence agreement is considered. The investigation mainly consists of a comparative analysis of EC competition law and American antitrust law concerning the economic arguments and their importance. The treatment of territorial restrictions, field of use restrictions, quantity clauses, tie-outs, tie-ins, grant back, no-challenge clauses and price restrictions are of special interest here. This study shows that an economically realistic view of competition has influenced current EC competition law, especially in the Technology Transfer Block Exemption Regulation (TTBER). Exceptions from this development in the EC law are mainly due to the goal of integration of the common market. Territorial restrictions are strictly regulated in the TTBER even when the parties’ market shares are below the market thresholds defined in the regulation. The function of intellectual property rights are not much considered in EC competition law but there are general remarks about the economic functioning of patents in the Guidelines for the TTBER. However, it is difficult to find evidence for economic reasoning about patents in the formation of concrete rules. On the contrary, patents are weakened by the widened concept of exhaustion presented in the Guidelines. The economic functioning of the licence agreement is considered in the rules of TTBER and the economic arguments for clauses which create incentives for making investments or give the possibility of control are acknowledged. However, the free riding argument has a weak position when applied to territorial restrictions, which are more formalistically regulated. The EC competition law has become more similar to American antitrust law. The decisive difference consists in the judicial treatment of territorial restrictions, where the goal of integration is still of central importance in EC law.
Keywords: Antitrust Law; Civilrätt; Competencia; Competition law; Immaterialrätt; Intellectual property; Know-how; Konkurrensrätt; Law and Economics; Licence agreement; Licensavtal; Licensing; Patent; Private law; Rättsekonomi; Technology transfer; Tekniköverföring

La notion de création intellectuelle - Ardoy, Pierre-Yves (Université de Pau et des Pays de l'Adour, 2006)
La création intellectuelle accompagne l’humanité. On peut même affirmer que c’est elle qui révèle l’homme à lui-même. Si le droit prend en considération la création en proposant un certain nombre de régimes spécifiques, la nature protéiforme de la propriété intellectuelle ne permet toutefois pas d’appréhender la création sous l’angle de l’unité. Or il s’agit bien d’une notion unitaire. L’étude tant du domaine (première partie) que des caractères (deuxième partie) conduit ainsi à montrer que la création intellectuelle est la manifestation objectivée d’une activité humaine, ce qui lui permet d’être appréhendée par le droit d’abord en tant que chose concrète, ensuite en tant que bien – droits portant sur la chose et sur ses utilités. Si l’on présente souvent la propriété intellectuelle comme étant le droit du reproductible, le caractère de reproductibilité de la création ne permet pas toutefois de la distinguer des autres choses. Il s’agit alors de chercher les spécificités de la création dans son origine, la volonté humaine. Aussi se dessine clairement l’idée que seule la liberté de l’agent –le créateur - dans la réalisation de l’objet –la création - permettra de caractériser une création. La liberté est donc non seulement le critère de la création en tant que produit de l’activité intellectuelle, mais elle est surtout la condition sine qua non de l’existence et de la reconnaissance de celle-ci.
Keywords: Dessins et modèles; Droit d'auteur; France; Intellectual property; Originalité; Propriedade intelectual; Propriété industrielle; Propriété intellectuelle

A comparative legal study of the dilution of registered trade marks in selected jurisdictions to further the development of the remedy in South African law - Van der Walt, Elizabeth Margaretha (Stellenbosch University, 2005)
Trade marks are among the most valuable commodities of the modern business world. Adequate protection for trade marks to prevent the misappropriation of their incredible marketing power is therefore important. The aim of this dissertation is to make recommendations regarding the further development of existing South African law regarding the protection of registered trade marks against dilution, particularly by the courts. Current statutory protection is examined and compared with trade-mark law in the United States and the European Union. Although the concept of dilution originated in Germany, most of its development took place in the United States, starting in 1927 with an article by Frank Schechter. Dilution occurs when the awareness that a specific mark signifies a single product from a single source changes to an unmistakable awareness that the same mark signifies various things from various sources. The primary theories as to how dilution occurs are blurring and tarnishment. Although the dilution concept is widely recognised, there is still a debate amongst legal scholars on whether trade marks deserve protection against dilution. The extent of protection that the law gives to trade marks largely depends on the socioeconomic functions that a trade mark is perceived to fulfil. The original source or origin function is protected by the traditional infringement provisions. The identification or distinguishing function, quality function and advertising function subsequently gained recognition. The advertising function is statutorily recognised in various jurisdictions, which prevents trade-mark dilution. Statutory recognition of dilution in the United States first occurred in State law from 1947 onwards. Protection is generally given to distinctive or strong trade marks where a similar mark is used on dissimilar goods in the absence of confusion in such a way that there is a likelihood that the reputation of the senior mark will be injured. The parameters of the concept were developed and refined mainly through case law. Federal protection against dilution was only introduced in 1995. The new Act, although widely welcomed, also brought some unpredictability and interpretation problems. The first statutory dilution protection for trade marks in Europe is found in the Uniform Benelux Trade Marks Act. In 1989 the European Union adopted the Trademark Directive, with the aim of harmonising the legal protection afforded to trade marks. Its "dilution" provisions were incorporated into the United Kingdom's Trade Marks Act of 1994. The sometimes conflicting interpretations of these provisions by the English courts and the Court of Justice of the European Communities are discussed. The South African Act shows a substantial degree of harmony with legislation in the United Kingdom and other European countries. Aspects of the wording of the dilution provisions are however open to interpretation by the courts. Until the end of 2003 there was only one major trade-mark dilution case decided by a South African court, namely SAR v Laugh It OjJPromotions, which is discussed in detail. The dissertation concludes with recommendations to aid South African courts in the future interpretation and application of the dilution provisions. Amendments to the legislation are also proposed to promote greater clarity.
Keywords: Brand name products; Comparative law; European Union countries; Intellectual property; South Africa; Trademarks; United States

L'intérêt du public en droit d'auteur. Tome 1 - Carre, Stéphanie (Université Montpellier 1, 2004)
Le droit d'auteur est traditionnellement conçu comme le droit de l'auteur. L'approche personnaliste conduit à une analyse tournée vers la personne du créateur. On ne saurait pourtant négliger la relation triangulaire entre l'auteur, l'exploitant et le public autour de l'œuvre et particulièrement l'indissociabilité de l'auteur et du public à son égard. D'ailleurs, si l'intérêt de l'auteur est mis en avant, le législateur a dès l'origine, pris en compte celui des destinataires. Dans cette perspective, l'étude de l'intérêt du public permet de mieux comprendre le droit d'auteur, d'en saisir l'évolution et les raisons de la «crise» du droit d'auteur. Le discours visant aujourd'hui à affirmer les «droits» du public en tant que droits supérieurs devant lesquels devraient s'incliner ceux de l'auteur, qui tend à réduire la réflexion relative au public à la question de son droit à l'information et à présenter en termes d'opposition irréductibles les intérêts de l'auteur et du public, appelle également cette réflexion sur l'intérêt du public en droit d'auteur. Il était essentiel de souligner que les relations entre ces intérêts ne peuvent être réduites à une stricte opposition et de montrer que le droit d'auteur ne méconnaît ni l'intérêt de l'auteur, ni celui du public.
Keywords: Droit d'auteur; Intellectual property; Intérêt général; Propriedade intelectual; Propriété intellectuelle

L'intérêt du public en droit d'auteur. Tome 2 - Carre, Stéphanie (Université Montpellier 1, 2004)
Le droit d'auteur est traditionnellement conçu comme le droit de l'auteur. L'approche personnaliste conduit à une analyse tournée vers la personne du créateur. On ne saurait pourtant négliger la relation triangulaire entre l'auteur, l'exploitant et le public autour de l'œuvre et particulièrement l'indissociabilité de l'auteur et du public à son égard. D'ailleurs, si l'intérêt de l'auteur est mis en avant, le législateur a dès l'origine, pris en compte celui des destinataires. Dans cette perspective, l'étude de l'intérêt du public permet de mieux comprendre le droit d'auteur, d'en saisir l'évolution et les raisons de la «crise» du droit d'auteur. Le discours visant aujourd'hui à affirmer les «droits» du public en tant que droits supérieurs devant lesquels devraient s'incliner ceux de l'auteur, qui tend à réduire la réflexion relative au public à la question de son droit à l'information et à présenter en termes d'opposition irréductibles les intérêts de l'auteur et du public, appelle également cette réflexion sur l'intérêt du public en droit d'auteur. Il était essentiel de souligner que les relations entre ces intérêts ne peuvent être réduites à une stricte opposition et de montrer que le droit d'auteur ne méconnaît ni l'intérêt de l'auteur, ni celui du public.
Keywords: Droit d'auteur; Intellectual property; Intérêt général; Propriedade intelectual; Propriété intellectuelle

Propriété intellectuelle et indivision - Robin, Agnès (Université Montpellier 1, 2001)
La confrontation que propose cette étude de la notion de propriété intellectuelle avec celle d'indivision révèle, malgré la différence d'âge (vingt-sept siècles) qui les sépare, toute la richesse de leur mutuelle rencontre. La lecture de la propriété intellectuelle à travers le prisme de la définition de l'indivision, qui est un concours de droits de propriété sur une chose unique, a permis, non seulement de constater toute la vigueur consacrée par la réforme du 31 juillet 1976 que recèle l'institution mais aussi de révéler les multiples occasions pour les biens incorporels que sont les créations intellectuelles (oeuvre de l'esprit, brevet, marque, etc. ) d'y trouver refuge. La collaboration étant un processus de création en expansion, l'indivision ne peut plus être réduite à une situation subie ainsi confinée aux seules hypothèses de transmission successorale. La réalité de la propriété intellectuelle indivise se trouve confortée par la cohérence de sa mise en œuvre. L'examen de l'exercice de la propriété intellectelle montre en outre la souplesse que l'ubiquité de la création confère au système d'ensemble. La propriété intellectuelle indivise autorise, de fait, une utilisation simultanée de la création permettant aux copropriétaires de s'affranchir, sans y déroger, de certaines régles contraignantes de l'indivision et de relativiser la nécessité pratique, mais non théorique, de procéder au partage. Loin d'être la "mère des procès", l'indivision se voit ainsi stabilisée et réhabilitée au profit, et non plus au détriment, des personnes participant de près ou de loin à la création intellectuelle.
Keywords: Brevet; Competencia; Concurrence; Copropriété; Disposition; Droit de propriété; Droit d’auteur; Droits réels; Démembrement; Exploitation; Indivision; Intellectual property; Jouissance; Marque; Partage; Propriedade intelectual; Propriété intellectuelle; Usufruit